2011
DOI: 10.1038/hdy.2011.105
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal dynamics of nucleolar organizer regions (NORs) in the house mouse: micro-evolutionary insights

Abstract: Variation in the number and chromosomal location of nucleolar organizer regions (NORs) was studied in the house mouse, Mus musculus (2n¼40). From an origin in Western Asia, this species colonized the Middle East, Europe and Asia. This expansion was accompanied by diversification into five subspecies. NOR diversity was revealed by fluorescence in situ hybridization using 18S and 28S probes on specimens spanning Asia to Western Europe. The results showed that the house mouse genome possessed a large number of NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 38 publications
(77 reference statements)
2
46
0
Order By: Relevance
“…The variation in NORs size and/or location has been frequently reported in various vertebrates [e.g. Gornung et al, 2011;Britton-Davidian et al, 2012;Gornung, 2013]. Therefore, we suggest that the polymorphism of the XJA pair can be attributed to the variation in the numbers of copies of the rDNA gene.…”
Section: Javanicus Is the Single Representative Of The Genusmentioning
confidence: 80%
“…The variation in NORs size and/or location has been frequently reported in various vertebrates [e.g. Gornung et al, 2011;Britton-Davidian et al, 2012;Gornung, 2013]. Therefore, we suggest that the polymorphism of the XJA pair can be attributed to the variation in the numbers of copies of the rDNA gene.…”
Section: Javanicus Is the Single Representative Of The Genusmentioning
confidence: 80%
“…As the NORs of most Mus musculus subspecies are located on six autosomes and as are all centromerically located (Britton-Davidian et al 2012;Gibbons et al 2015), it was initially suggested that rDNA might be a player for the peripheral NPB localization of pericentromeres. However, 3D mapping of rDNA by DNA-FISH in the zygote revealed that chromosomes without NORs also associate with NPBs, and not all rDNA-bearing chromosomes have their centromeres on the NPB surface, but some sit close to the nuclear periphery (Aguirre-Lavin et al 2012).…”
Section: Chromatin Organization Of the Preimplantation Embryomentioning
confidence: 99%
“…To date, the DNA requirement and molecular mechanism allowing the propagation through mitosis of human nucleoli remain to be elucidated. The positioning of rDNA arrays within heterochromatic regions is an evolutionarily conserved feature (Henderson et al 1972;Britton-Davidian et al 2012), hinting at a role for chromosome context in nucleolar biology. Furthermore, even though acrocentric chromosome p-arms are still missing from current human genome assemblies, our recent work has established that sequences surrounding rDNA arrays are conserved among all human acrocentric chromosomes (Floutsakou et al 2013).…”
mentioning
confidence: 99%